Eat Widely, Vote Wisely: Lessons from a Campaign against Vote Buying in Uganda - Christopher Blattman; Horacio Larreguy; Benjamin Marx; Otis Reid (CESifo GmbH, 2024)
We study a large-scale intervention designed by civil society organizations to reduce vote buying in Uganda's 2016 elections. We study this intervention in light of a model where incumbents benefit from a first-mover and valence advantage, vote buying and campaigning are complementary, and voter reciprocity increases the effectiveness of vote buying. The intervention undermined reciprocity as well as the valence advantage of incumbents. As a result, challengers not only campaigned more intensively but also bought more votes in treated locations. Consistent with incumbents being first movers in markets for votes and facing more frictions to adjust their strategies than challengers, their response to the intervention was limited. The intervention ultimately failed to reduce vote buying, but led to short-run electoral gains for challengers and increased service delivery in treated locations.
Keywords: C93; D72; O55; 330; elections; voting behaviour; field experiment; Africa